2001
DOI: 10.1126/science.1062977
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Sensory Rhodopsin II at 2.4 Angstroms: Insights into Color Tuning and Transducer Interaction

Abstract: We report an atomic-resolution structure for a sensory member of the microbial rhodopsin family, the phototaxis receptor sensory rhodopsin II (NpSRII), which mediates blue-light avoidance by the haloarchaeon Natronobacterium pharaonis. The 2.4 angstrom structure reveals features responsible for the 70- to 80-nanometer blue shift of its absorption maximum relative to those of haloarchaeal transport rhodopsins, as well as structural differences due to its sensory, as opposed to transport, function. Multiple fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
369
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(400 citation statements)
references
References 39 publications
25
369
1
5
Order By: Relevance
“…In other words, these results strongly suggest that the counterpart of the C 14 D group is Thr204, not Tyr174. This is consistent with the X-ray structures of SRII and SRII K , where the distance from the C 14 atom changes from only 4.0 to 3.9 Å for the phenol oxygen of Tyr174, and a larger change from 4.4 Å to 3.3 Å occurs for the hydroxyl oxygen of Thr204 (7,11). It also should be noted that the peak frequency is upshifted to 2251 cm -1 for Y174F, and the broadened band implies conformational heterogeneity for the C 14 D group (spectrum e of Figure 2A).…”
Section: C-d Stretching Vibrations Of the Retinal In Srii K Of Mutantsupporting
confidence: 89%
See 2 more Smart Citations
“…In other words, these results strongly suggest that the counterpart of the C 14 D group is Thr204, not Tyr174. This is consistent with the X-ray structures of SRII and SRII K , where the distance from the C 14 atom changes from only 4.0 to 3.9 Å for the phenol oxygen of Tyr174, and a larger change from 4.4 Å to 3.3 Å occurs for the hydroxyl oxygen of Thr204 (7,11). It also should be noted that the peak frequency is upshifted to 2251 cm -1 for Y174F, and the broadened band implies conformational heterogeneity for the C 14 D group (spectrum e of Figure 2A).…”
Section: C-d Stretching Vibrations Of the Retinal In Srii K Of Mutantsupporting
confidence: 89%
“…According to the X-ray structure of SRII (11), the distance from the C 14 atom to the phenol oxygen of Tyr174 is 4.0 Å, to the hydroxyl oxygen of Thr204 is 4.4 Å, and to the hydroxyl oxygen of Thr79 is 4.3 Å (Figure 1b). The structure of SRII K shows that only the distance to Thr204 is significantly reduced, from 4.4 to 3.3 Å, by retinal photoisomerization (7,11). This result suggested that Thr204 may be the counterpart of the C 14 D group (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of intermediates designated J, K, L, M, N, and O are defined by spectroscopy, and M (M 410 ), which has an absorption peak at 410 nm and the longest lifetime, is only the intermediate containing a deprotonated Schiff base [134]. The light-induced conformational changes in bR in the frozen activated state of the wild type (WT) and bR mutants have been studied by x-ray crystallography and electron microscopy [137][138][139]. The extent of the changes reported varies depending on the methods used, but it is generally small (0.1−0.3 nm).…”
Section: Br In Response To Lightmentioning
confidence: 99%
“…Subsequently, the heterologous expression of functional pSRII from N.pharaonis has been achieved in E. coli [15] followed by expression of BR, HR and SRI from H. salinarum and purification by one step metal affinity chromatography [16,17]. Functional expression of pSRII made it possible to obtain sufficient protein for structural investigation of the receptor alone [18,19] as well as in complex with its cognate transducer [20].…”
Section: Introductionmentioning
confidence: 99%